Microbiota in the Rhizosphere and Seed of Rice From China, With Reference to Their Transmission and Biogeography - Zhou, Xin; Wang, Jin-Ting; Zhang, Zhi-Feng; Li, Wei; Chen, Wen; Cai, Lei (Frontiers in Microbiology, 2020)
Seeds play key roles in the acquisition of plant pioneer microbiota, including the transmission of microbes from parent plants to offspring. However, the issues about seed microbial communities are mostly unknown, especially for their potential origins and the factors influencing the structure and composition. In this study, samples of rice seed and rhizosphere were collected from northeast and central-south China in two harvest years and analyzed using a metabarcoding approach targeting 16S rRNA gene region. A higher level of vertical transmission (from parent seed microbiota to offspring) was revealed, as compared to the acquisition from the rhizosphere (25.5 vs 10.7%). The core microbiota of the rice seeds consisted of a smaller proportion of OTUs (3.59%) than that of the rice rhizosphere (7.54%). Among the core microbiota, species in Arthrobacter, Bacillus, Blastococcus, Curtobacterium, Pseudomonas, and Ramlibacter have been reported as potential pathogens and/or beneficial bacteria for plants. Both the seed and the rhizosphere of rice showed distance-decay of similarity in microbial communities. Seed moisture and winter mean annual temperature (WMAT) had significant impacts on seed microbiota, while WMAT, total carbon, available potassium, available phosphorus, aluminum, pH, and total nitrogen significantly determined the rhizosphere microbiota. Multiple functional pathways were found to be enriched in the seed or the rhizosphere microbiota, which, to some extent, explained the potential adaptation of bacterial communities to respective living habitats. The results presented here elucidate the composition and possible sources of rice seed microbiota, which is crucial for the health and productivity management in sustainable agriculture.